Адміністрування, мотивування й комунікації як елементи управлінського лідерства в системі менеджменту персоналу підприємств - Бочарова, Наталія Олександрівна; Bocharova, Nataliia (Мелітополь : ТДАТУ, 2021)
UA: В статті проаналізовано та обґрунтовано сучасні підходи до оцінки складових управлінського лідерства в системі менеджменту персоналу підприємств за умов невизначеності та надано їх практичну апробацію з акцентуванням на аспектах комунікації, мотивування та адміністрування для працівників сучасних підприємств України. EN: The basis of an effective personnel management system are the levers of administration, communication and leadership, supported by the latest motivation mechanism. Almost all of them are sensitive to the demands of a market economy. Almost all of them are sensitive to the demands of a market economy. At the same time, the key aspect of effective personnel management is leadership skills, knowledge of psychology and communicative management. At the same time, the key aspect of effective personnel management is leadership skills, knowledge of psychology and communicative management. Administration is a mechanism, motivation is a means, communication is a wrapper on the way to forming a portrait of an effective manager. That is, a successful combination of means of administration, motivation and communication is the key to forming the personality of the leader as an effective leader who can ensure the implementation of a system of highly effective management of the enterprise. It is the formation, disclosure and ability to retain an effective employee is the purpose of the personnel management system of any enterprise in a transitive economy of Ukraine. According to research, ninety percent of the success of the company is formed by an effective leader - the leader and only ten percent - is directly the reputation and positive business image of the employer organization. These aspects should be placed in the symbiosis of administration, motivation and communication as a guarantee of synergy in personnel management. The common intersection of each of these processes is the moment of leadership. It should be interpreted as a certain attempt to influence the manager on the employee in order to obtain a certain result to achieve a certain goal. And it is the means of administration (organization - division and cooperation, sometimes even through the prism of bureaucratic approaches; team building, individual and team changes, etc.), motivation (encouragement and stimulation to highly productive work) and communication (suggestion, persuasion, even suggestion, etc.) are effective tools on the way to the formation of a balanced system of leadership in the personnel management of modern enterprises.
Administration, motivation and communication as elements of management leadership in the enterprise personnel management system
Keywords: адміністрування; ефективність менеджменту персоналу; комунікації; лідерство; механізм менеджменту підприємств; персонал; система мотивації праці; управління персоналом підприємств; стилі управління; administration; efficiency of personnel management; communication; leadership; mechanism of enterprise management; personnel labor motivation system; management style; personnel management of enterprises